Identifikasi Jamur Pathogen pada Air Bak Toilet SPBU di Kecamatan Rumbai Kota Pekanbaru - Mega Pratiwi Irawan; Siti Juariah; Syarifah Rukmaini (Poltekkes Kemenkes Kendari, 2019)
Water is a source of disease transmission. Many water-borne diseases are caused by contamination by bacteria, viruses, parasites and fungi. Fungal contamination of water comes from water sources that are not properly maintained. Lacto Phenol Cotton Blue (LPCB) solution serves to color the mushrooms blue. The purpose of this study was to determine the pathogenic fungi found in the water of gas stations in Rumbai District, Pekanbaru City. This research was conducted using experimental methods in the laboratory. Laboratory tests include planting on PDA (Potato Dextrose Agar) media using the pour plate method. The identification was carried out macroscopically by looking at the shape and color of the colony, and microscopically using the LPCB solution. The results obtained from this study were mostly found Candida fungi and there are also other fungi such as Aspergillus, Trichophyton, Penicillium. From the results obtained, it was concluded that in the toilet water of gas stations in Rumbai District, Pekanbaru City, found pathogenic fungi.